The immune cells causative role in lung cancer: Mendelian randomization study - Qianhui Zhou; Yanchao Liang; Xun Chen; Siwei Qi; Lanlan Wei (Discover Oncology)
Abstract Backgrounds Lung cancer (LC) is the leading cause of cancer-related deaths in China, with its incidence and mortality rates rising annually. Various studies have demonstrated disparities in immune cell counts and profiles between LC patients and healthy individuals. However, the existence of a causal link remains largely uncertain. To explore the potential causal association between immune cells and LC risk, a Mendelian randomization (MR) approach was employed. Methods Employing immune cell genome-wide association study (GWAS) data from a public database (n = 731 subjects) and Lung Cancer Genome Research Consortium's GWAS dataset (n = 492,803 participants), unconventional genetic loci remarkably associated with the significant abundance of 731 types of immune cells were extracted according to preset threshold points as instrumental variables. The primarily analytical strategy involved the inverse variance weighting (IVW) method, with the effect size estimates expressed as odds ratio (OR) and 95% CI. The robustness of the findings was assessed through a leave-one-out sensitivity analysis, heterogeneity test, horizontal gene pleiotropy test, MR-PRESSO and MR-Egger. Results The MR analysis identified a significant association between 18 distinct immune cell types and lung cancer risk. MR analysis revealed that 7 types of immune cells, including CD20 on IgD − CD38 − B cell, CD20 on switched memory B cell, IgD on IgD + CD24 + B cell, BAFF − R on IgD − CD38 + B cell, CD39 + resting CD4 regulatory T cell Absolute Count, CD127 on CD45RA + CD4 + T cell, CD8 on Effector Memory CD8 + T cell, displayed a protective effect against lung cancer development. Conversely, 11 other immune cells populations were positive associated with an increased lung cancer risk. In contrast, reverse MR analysis indicated that the lung cancer risk was linked to 11 immune cells, with 2 types of immune cells (CD25 on IgD − CD27 − B cell, CD4 + T cell %leukocyte) showing a are positive correlation with cancer development, whereas 9 types of immune cells appeared to be inversely regulated. These findings collectively imply that specific immune cell populations may play critical roles in either promoting or suppressing the initiation and progression of lung cancer. Conclusion The findings of this study offer fresh insights into the underlying biological mechanisms governing lung cancer development, thereby opening new avenues for future research in the domain of LC. The identification of specific immune cell subsets with protective or promoting roles provides crucial leads for preventive and therapeutic strategies. These insights have the potential to enhance early detection methods and inform the development of more effective treatment approaches, ultimately benefiting patient outcomes and improving the overall management of lung cancer.